Identification of determining factors size and shape Simbal cattle and Brahman Cross cattle in Pamenang Barat Merangin district - Fitra Diansah; Depison Depison; Silvia Erina (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2021)
This study aims to determine the determinants of size and shape of Simbal and Brahman Cross cattle in the West Pamenang sub-district, Merangin district. The method of this study was a survey with a purposive sampling technique. Sampling criteria included: Sample of each breeds consisted of 60 Simbal and 60 Brahman Cross cattle aged 1-2 years. Data observed included: body length, shoulder height, chest circumference, inside chest, chest width, canon circumference, hip height, body weight, and body weight gain. The differences in body measurements between Simbal and Brahman Cross cattle analyzed by T-test. Identification of the determinants of size and shape of Simbal and Brahman Cross cattle were analyzed using Main Component Analysis method. The results of this study were body weight, body weight gain, and body measurements of Simbal cattle were significantly different (P <0.05) higher than Brahman Cross cattle, both male and female. Simbal cattle and male Brahman Cross cattle were significantly different (P <0.05) higher than females. The conclusion shows that body weight, body weight gain, and body measurements of Simbal cattle are higher than Brahman Cross cattle. Male body weight gain was higher than females in both Simbal and Brahman Cross cattle. The determining factor for the body size of Simbal and Brahman Cross cattle is chest circumference, while the determining factor for body shape of Simbal cattle is the height of shoulders, while Brahman Cross is body length. The highest correlation between body measurements and body weight in Simbal and Brahman Cross cattle, both male and femal is chest circumference (LD).